Ploidy Level Influences Pollen Tube Growth and Seed Viability in Interploidy Crosses of Hydrangea macrophylla - Alexander, Lisa (Frontiers in Plant Science, 2020)
Hydrangeas, prized for their large showy flowers and lush green foliage, are sold for landscape use, patio and container use, and as cut flowers in the floral industry. All H. macrophylla cultivars tested to date are diploid (2n=2x=36) or triploid (2n=3x=54) and triploid H. macrophylla have thicker stems, larger flowers, and larger stoma compared to related diploids. It is unknown whether interploidy crosses between diploid and triploid hydrangeas can be used to develop triploid varieties. The objective of this study was to compare pollen tube development, fruit formation, and seed viability among intra- and interploidy pollinations of Hydrangea macrophylla and evaluate the genome size, pollen and pollen viability of resultant progeny. By 24 h post-pollination, pollen tubes had reached the ovaries of diploid flowers in 48.7% of samples while pollen tubes reached the ovaries in only 8.7% of triploid flowers (χ2 = 30.6, p < 0.001). By 48 h post-pollination pollen tubes reached the ovaries of diploid and triploid flowers in 72.5% and 53.8% of samples, respectively (χ2 = 26.5, p = 0.001). There was no difference in percentage of flowers with pollen tubes reaching the ovaries in diploid and triploid flowers at 72 h after pollination (χ2 = 7.5, p = 0.60). Analysis of covariance showed that pollen tube length at 24 and 48 h post-pollination was significantly influenced by ploidy and flower length of the female parent. Progeny of interploidy crosses were diploid and aneuploid; no triploid progeny were recovered from crosses using triploid parents. Mean genome sizes of offspring from each cross type ranged from 4.4 for 2n × 2n offspring to 5.2 for 3n × 3n offspring. Estimated ploidy of offspring ranged from 2n for 2n × 2n crosses to 2n + 5 for 3n × 3n crosses. Pollen stainability rates of flowering offspring ranged from 69.6% to 76.4%. The progeny from interploidy hybridizations have broad potential in breeding programs to provide genetic and phenotypic variability for the production of novel varieties.